Biodiversity of medicinal plants in north east India: their systematic utilisation (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Â North eastern India comprising of eight states namely Assam, Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim and Tripura is widely rich in biodiversity belonging to different climatic conditions varying from tropical subtropical, temperate and alpine zones which covers the major occurrence of medicinal plants. The different states of North east India are falling into different hill zones like Eastern Himalaya beginning from Sikkim to Lohit district of Arunachal Pradesh, Naga hills covering the areas of Nagaland and Manipur states, Lusai hills with Mizoram and Tripura states and Garo, Jayantiya and Khasi hills occupying the state of Meghalaya. The biodiversity distribution extents even to neighbouring countries like China, Mayayanmar and Bangladesh. Classification of different hills of north eastern India provides the distribution of specific medicinal plants like Sikkim is the richest source for Berginia ciliate, Cordiceps sinensis, Hippophae species, Nardostachys jatamansi, Picrorrhiza kurrooa, Swertia chirayita; Arunachal Pradesh for Acorus calamus, Aquillaria agallocha, Â Berberis aristata, Cinnamomum tamala, C. zeylanica, Coptis teeta, Cordiceps sinensis, Embelia ribes, Paris polyphylla, Rubia cordifolia, Gynocordia odorata, Illicium griffithii, Taxus wallichiana, Valeriana jatamansi; Nagaland and Manipur for Smilax glabra, Asparagus adscendens with less occurrence of Rubia cordifolia, Taxus wallichiana, Thallictrum foliolosum etc; Jayantiya hill of Meghalaya comprises of wider distribution of Embelia ribes; Lusai hill covering the state of Mizoram and eastern plains of Tripura comprises of Holorhena antidysenterica, Mallotus phillippinensis, Saraca asoka, Smilax glabra, Stephania glabra and Terminalia chebula. Plants belonging to Zingiberaceae like Curcuma aromatica, C. caesia, C. zedoaria, Hedychium coronerium, H. spicatum and Phyllanthus amaras are widely distributed in foot hills of Arunachal Pradesh and other north eastern states and adjoining part of Assam. Various cultivation practices have developed the sites for cultivation of Alstonia scholaris, Andrographis paniculata, Asparagus racemosus, Elaeocarpus sphericus, Mesua ferrea, Oroxylum indicum etc. in the tropical region. Paper deals with various cultivation practices of some of the high demand medicinal plants in north eastern states.